ANALISIS STRATEGI PEMASARAN DAN PENJUALAN E-COMMERCE PADA PT WOOK GLOBALTECHNOLOGY - Arif Azmi; S. S. Admadja (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
The continuous development of Internet technology has created a myriad of new opportunities for society, particularly in the realm of business. E-COMMERCE, in particular, has made buying and selling transactions more practical and accessible, allowing them to be conducted online at any time without time constraints. Wook is an E-COMMERCE platform that connects well-known Chinese brands with retail traders in Indonesia. Through the WOOK application, consumers can explore a wide range of products, including cellphone accessories, computer accessories, gaming devices, stationery equipment, and household furniture, all of which are of high quality and offered with enticing promotions. Furthermore, buyers need not worry about the delivery of goods or customs administration. Thanks to the WOOK application, consumers can shop from the comfort of their homes while still enjoying relatively affordable prices, whether they are buying in large or small quantities. Therefore, this study aims to analyze the Business-to-Business (B2B) type of E-Commerce marketing strategy using content analysis to provide insights into enhancing the effectiveness and efficiency of marketing strategies through E-commerce. This research is qualitative and descriptive in nature, with data collected through observations and interviews. Employing content analysis and deductive analysis, this study examines the E-Commerce marketing strategy on the Wook Platform. The study's findings reveal that Wook is the first B2B (Business to Business) E-Commerce platform in Indonesia that conducts large-scale sales to master dealers and resellers. Wook's products are of the highest quality and come with clear warranties.